2018
DOI: 10.2485/jhtb.27.160
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Enamel Surface Morphology and Microhardness after the Application of Different Protective Agents

Abstract: The aim of this in vitro study was to compare the eff ect of diff erent protective agents on the surface microhardness and morphology on enamel eroded by a cola drink. Sixty sound anterior teeth were randomly divided into fi ve groups. The baseline surface microhardness of the enamel was measured. For demineralization procedures, all teeth were immersed in cola for 8 minutes and surface microhardness was remeasured. The fi ve groups for remineralization procedures were defi ned as: Group 1: Artifi cial saliva,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
1
1
Order By: Relevance
“…They attributed their finding to the ability of the low-viscosity resin to fill the spaces between the remaining crystals of the porous lesions and re-harden the demineralized tissue, thereby improving their mechanical strength. Also, this result is in disagreement with Simsek, et al, (20) who found there were no significant increases in the surface microhardness values of artificial saliva or CPP-ACP. They attributed their findings to CCP-ACP being more effective in deep caries lesions.…”
Section: Discussioncontrasting
confidence: 87%
“…They attributed their finding to the ability of the low-viscosity resin to fill the spaces between the remaining crystals of the porous lesions and re-harden the demineralized tissue, thereby improving their mechanical strength. Also, this result is in disagreement with Simsek, et al, (20) who found there were no significant increases in the surface microhardness values of artificial saliva or CPP-ACP. They attributed their findings to CCP-ACP being more effective in deep caries lesions.…”
Section: Discussioncontrasting
confidence: 87%
“…However, whether resin composites exposed to these agents cause surface degradation has been a matter of concern. Researchers have investigated whether these agents, which are applied for protective purposes in dentistry, cause surface changes such as surface roughness, microhardness, and elemental changes in resin-based composites [ 4 , 42 – 44 ]. Since APF gels contain strong acids, the composition and surface integrity of composites and other glass-containing restoratives can change significantly.…”
Section: Discussionmentioning
confidence: 99%